How about some critical soup? - Abraham, Danna (Murmurations: Journal of Transformative Systemic Practice, 2025)
This poem emerged from the raw data material of the author’s most recent teaching evaluations in higher education, recasting the very phrases and opinions that often remain, decontextualized and invisible in the educator’s official records. Rather than accepting the felt judgments that often do harm, the poem reworks reviewers’ bolded sentences into a counter-narrative that centres the context of classroom dynamics and relational learning - transforming deficits into narrative coherence. Additionally, this poem illustrates how reviewers’ feedback, when clipped from its classroom context, can be situated into surveillance practices of women’s tone as well as feminist critique that often flattens relational learning. By repurposing those words as another act of rebellion, the poem reframes criticism as a site of meaning-making. It moves from accusation to invitation, from rating to reflection, and from surveillance to shared responsibility. The inspiration for this writing is situated in the lived realities of the author - a woman of colour - who has written about embracing poetry as a transformative practice in educational environments (Abraham, 2024). The author invites readers through the journey of reconsideration - from receiving student feedback in the form of teaching evaluation that is centred in anonymity to building dialogic, context-rich response to the felt damages of a consumer-style feedback system.